COMBINED TREATMENT WITH TOTAL PARENTERAL NUTRITION, NASOPANCREATIC DRAINAGE AND SMS 201-995 IN EXTERNAL PANCREATIC FISTULA - M. Emin CANER; A. Sedat BOYACIOĞLU; M. Enver DOLAR; K. Bahri ATEŞ; Burhan ŞAHİN (Turkish Journal of Gastroenterology, 2020)
-